Implementasi Pembelajaran Mendalam melalui Media Interaktif Berbasis Teknologi di Madrasah Ibtidaiyah - M. Ekhzan Natha Pratama; M. Mawardi (Yayasan Sagita Akademia Maju, 2026)
This study aims to describe the implementation of deep learning through technology-based interactive media in Madrasah Ibtidaiyah. Deep learning is an approach that emphasizes comprehensive understanding of concepts, critical thinking skills, creativity, and active student involvement in the learning process. The research method used was a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that the use of technology-based interactive media was able to increase students’ learning interest, participation, and understanding of learning materials. In addition, interactive media helped teachers create a more engaging, effective, and innovative learning environment. The implementation of deep learning through technology also provided opportunities for students to learn actively, independently, and collaboratively. The obstacles found included limited technological facilities and teachers’ ability to operate digital media optimally. Nevertheless, technology-based learning remains one of the effective alternatives for improving the quality of education in Madrasah Ibtidaiyah in the digital era.